Tourism Spaces and their Transformation in the Contemporary World - Liszewski , Stanisław (Turyzm/Tourism, 2006)
The author’s aim is to find answers to a number of questions: is tourism space homogenous or are there different tourism spaces, and what are the spaces created during tourism activity? As a result of his research, the author has identified three general types: imaginative tourism spaces (A), 'access-restricted' tourism spaces (B) and real tourism spaces (C), as well as several tourism sub-spaces which are also discussed and described. In conclusion the author suggests that tourism space, or spaces, should become research theme in tourism studies.